Description of Level Medication Compliance For Hypertensive Patients at Santa Elisabeth Hospital Medan Heart Clinic - Murni Sari Dewi Simanullang; Friska Br. Sembiring; Amnita Anda Yanti Ginting; Ester Kristina Sitinjak (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2025)
Hypertension is a chronic disease that shows blood pressure above normal limits and is a global health problem and is a risk factor for cardiovascular disease. Treatment adherence is defined as the patient's level of willingness and the extent to which they strive and behave to follow medical directives, regulations, or recommendations provided by healthcare professionals in an effort to assist the patient's recovery. Adherence to taking medication allows patients to keep their blood pressure stable in order to avoid complications. This study aims to see the compliance of hypertension drug patients at the Heart Poly of Santa Elisabeth Hospital Medan in 2024. The research method used is a descriptive approach. The population in this study is 178 people, the number of samples is 82 people. Sampling technique with accidental sampling technique. The results of the study showed that from 82 respondents, the data obtained that the most age respondents were 38-53 years old with a total of 36 respondents (47.6%), the data on the most gender respondents were women as many as 48 respondents (48.5%), the data on the most education respondents was education as many as 32 respondents (39%), the data on the most respondents suffering from hypertension was 2 years of hypertension as many as 24 respondents (29.3%). The picture of the level of drug compliance of hypertension patients at the Heart Polyclinic of Santa Elisabeth Hospital Medan in 2024 is at a moderate level of 31 respondents (37.8%).